Analisis Noise Sinyal Bluetooth Pada Sistem Pintu Otomatis Berbasis Smart Home - Nirwana Haidar Hari; Sandy Vikki Ariyanto (Program Studi Sistem Informasi, 2019)
Automatic doors are generally developed by RFID cards or use cards with barcode labels. According to [1] the weakness of RFID is that the reading distance of the RFID Card is around 5 cm. According to [2] cards with barcode labels still have weaknesses such as barcode labels that are scratched, so that it cannot be identified. From RFID and barcode labels weaknesses, then an automatic door was designed using Arduino Uno with the Bluetooth module and controlled using an application on a smartphone instead of a card. Automatic doors with Android-based smartphone locks have several advantages, namely the ease, practically and relative security of losing keys. This technology is not yet commonly used by the people of Indonesia and is expected to be an alternative going forward as a solution in applying the concept of housing with smart technology. The purpose of this study is to design an automatic door using a Bluetooth signal connection and analyze the signal strength connected with a smartphone. The Bluetooth module used is the HC-05 module which operates at 2.4GHz frequency. According to [7] to produce a good Bluetooth connection, it is necessary to control and filter noise. The method in this research is to design an automatic door and then analyze the signal strength and signal range from the smartphone to the door. Smart home-based door systems with Android smartphone door locks can be used normally up to 9 meters and are considered sufficient for the size of a house in general.Keywords: automatic door, RFID card, Arduino Uno, bluetooth, smart home